POPULASI DAN KEANEKARAGAMAN MESOFAUNA SERASAH DAN TANAH AKIBAT PERUBAHAN TUTUPAN LAHAN HUTAN DI RESORT PEMERIHAN TAMAN NASIONAL BUKIT BARISAN SELATAN - Frendika Mahendra; Melya Riniarti; Ainin Niswati (EnviroScienteae, 2017)
This research was conducted to study about abundance and diversity of soil and litter mesofauna to the effect of forest cover change that occurred in the Pemerihan Resort, Bukit Barisan Selatan National Park. This research was compiled in a completely randomized design (CRD) and there were four different lands, which were: (1) primary forest, (2) coffee plantation, (3) corn field, and (4) grassland. The observation of mesofauna was taken in soil and litter from four different lands cover. The variable of observation were mesofauna abundance and diversity index, soil chemical properties (pH, organic carbon, total nitrogen, P available, and exchanged potassium), and soil physics properties (bulk density, soil temperature, humidity, and porosity). Data were analyzed using F test and further test using least significant differences (LSD) at 5%. The results showed that the different of lands cover affect the diversity index of litter mesofauna, the abundance of litter and soil mesofauna, yet did not affect the diversity index of mesofauna underground. However, the abundance and diversity index of soil and litter mesofauna in the primary forest was higher than the other lands.